Comparison of Fentanyl and Dexmedetomidine as Intrathecal Adjuvants to Spinal Anaesthesia for Abdominal Hysterectomy - Binod Gautam; Sushila Tabdar; Ujma Shrestha (Journal of Nepal Medical Association, 2018)
Introduction: Spinal anaesthesia, although advantageous for conducting abdominal hysterectomy, is not the first choice amongst surgeons for fear of intra-operative visceral pain. Intrathecal adjuvants may improve quality of spinal anaesthesia. This study aims to compare efficacy of intrathecal Fentanyl and Dexmedetomidine to reduce visceral pain during abdominal hysterectomy performed under spinal anaesthesia.